A finite element method to investigate the elastic properties of pillared graphene sheet under different conditions. (December 2018) - Song, Lubin; Guo, Zhangxin; Chai, Gin Boay; Wang, Zhihua; Li, Yongcun; Luan, Yunbo
Abstract: In this paper, an investigation was carried out to understand the mechanical elastic properties of a newly developed 3D nanocarbon structure material known as PGS (pillared graphene sheet). The effect of various parameters such as the pillared distance, the chirality, the volume fraction and the inclination angle of carbon nanotube on the elastic moduli was studied using the finite element method. The commercially available finite element software ABAQUS was utilized for the modelling and analysis of this new structure. Several different models were developed to study the effect of the various parameters mentioned earlier. Some interesting conclusions were deduced from the finite element investigation. It was found that the pillared distance, chirality and volume fraction affected the modulus significantly. The change in volume fraction impacted a bigger influence on the Young's modulus Ez and shear modulus Gxy . In some instances, Ez was increased by approximately 40 times. In addition, the Young's modulus Ez was also found to be affected by the change in the inclination angle and was shown to increase with increasing angle. Graphical abstract: Image 1